2006
DOI: 10.1186/1471-2407-6-20
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous localization of MLL, AF4 and ENL genes in interphase nuclei by 3D-FISH: MLL translocation revisited

Abstract: Background: Haematological cancer is characterised by chromosomal translocation (e.g. MLL translocation in acute leukaemia) and two models have been proposed to explain the origins of recurrent reciprocal translocation. The first, established from pairs of translocated genes (such as BCR and ABL), considers the spatial proximity of loci in interphase nuclei (static "contact first" model). The second model is based on the dynamics of double strand break ends during repair processes (dynamic "breakage first" mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…The breakage first hypothesis positions contact formation as an event secondary to DNA break formation. One of the reasons arguing against the contact first hypothesis was that 3D-FISH analysis indicated closer spatial proximity of MLL and ENL genes in interphase nuclei of myeloid (AML-193, PLB-985) and lymphoid cells (Nalm-6, IM-9) as compared with MLL and AF4 genes, even though AF4 represents the most frequent partner in MLL translocations (Gué et al, 2006 ). Evidence supporting breakage as the primary event leading to chromosome rearrangements was obtained also with the 3D time-lapse microscopy in living U2OS osteosarcoma cells using the fluorescently labeled 53BP1-GFP protein as a DSB marker.…”
Section: Replication Stalling or Transcription Stalling?mentioning
confidence: 99%
“…The breakage first hypothesis positions contact formation as an event secondary to DNA break formation. One of the reasons arguing against the contact first hypothesis was that 3D-FISH analysis indicated closer spatial proximity of MLL and ENL genes in interphase nuclei of myeloid (AML-193, PLB-985) and lymphoid cells (Nalm-6, IM-9) as compared with MLL and AF4 genes, even though AF4 represents the most frequent partner in MLL translocations (Gué et al, 2006 ). Evidence supporting breakage as the primary event leading to chromosome rearrangements was obtained also with the 3D time-lapse microscopy in living U2OS osteosarcoma cells using the fluorescently labeled 53BP1-GFP protein as a DSB marker.…”
Section: Replication Stalling or Transcription Stalling?mentioning
confidence: 99%
“…Triton X-100 combined with saponin and additional treatments such as repeated freeze thawing in liquid nitrogen were previously used to permeabilize human and mouse cell nuclei [ 4 , 26 , 29 , 30 ]. In these studies, an overall conservation of nuclear morphology and chromatin structure was reported.…”
Section: Discussionmentioning
confidence: 99%
“…Most protocols published thus far use either 80°C or higher temperatures for denaturation (e. g. 85°C, 94°C)[ 4 , 13 , 33 ]. In this study, thermal denaturation of Arabidopsis nuclei was performed at 70°C, 75°C, 88°C and 94°C in 50% formamide hybridization buffer.…”
Section: Discussionmentioning
confidence: 99%
“…Chromosomes occupy territories within the nucleus [6], suggesting another reason why DSBs at a certain locus may lead to a limited set of translocation products. For example, three-dimensional fluorescent in-situ hybridization (3D-FISH) analysis showed that mixed lineage leukemia (MLL) and its translocation partners, Eleven–nineteen leukaemia protein (ENL) and AML fused gene from chromosome 4 (AF4) are adjacently located in interphase nuclei [7]. Two factors that may regulate chromosome DSB end-coordination during NHEJ and homologous recombination are the Ku70/Ku80 heterodimer, which has end-binding, end-protection, and self-association activities, and the RAD50 subunit of the MRE11/RAD50/NBS1 (MRN) complex.…”
Section: Requirements For Chromosomal Translocationsmentioning
confidence: 99%